EFFECTIVENESS EVALUATION OF IMPLEMENTING “SCHOOL SAFETY ZONES” IN KEMAYORAN SUB-DISTRICT ELEMENTARY SCHOOLS - Venezia Novalira; Budi Hartanto Susilo (International Journal on Livable Space, 2023)
The increased chance of traffic accidents due to the increasing phenomenon of motor vehicle ownership due to increased sales figures. Most schools in the city of Central Jakarta are located in Kemayoran sub-district with many located on the roadside. Efforts to maintain safety are stated in the Regulation of the Director General of Land Transportation in the School Safe Zone or ZoSS guidelines. The study was conducted using an effectiveness survey with a characteristic classification method during entrance and after-school hours at SDN Utan Panjang 01 Pagi, SDN Sumur Batu 08 Pagi, and SDN Sumur Batu 01 Pagi. The research aims to determine the completeness of road equipment facilities, the effectiveness of ZoSS, and alternative solutions to maximize the ZoSS. The results show that among the three schools, the effectiveness of ZoSS SDN Utan Panjang 01 Pagi "Effective" with the most complete road equipment facilities including markings and signs, the effectiveness of ZoSS SDN Sumur Batu 08 Pagi "Effective" with road equipment facilities only signs, and the effectiveness of ZoSS SDN Sumur Batu 01 Pagi "Quite Effective" in the absence of road equipment facilities. Keywords : school safety zone, elementary school, speed, behavioral characteristics.